Comparative Analysis of Forest Fire Effects on Soil Degradation in Hilly vs. Plain Terrains (Integral Research, 2025)
Forest fires exert an influence on soil characteristics, nitrogen cycling and rate of deterioration so that the effects of forest fires are important ecological phenomena. This study investigates the effect of forest fires on topsoil properties of lowlands (Fatehpur Range) and hilly (Kosi Range) areas of Ramnagar forest division, Uttarakhand, India. The data collected and studied was of seasonal variation in soil pH, organic matter and nitrogen levels. The results show that topography affects fire effects and provides useful information to ensure sustainable management of forests.
Keywords: Forest fires, Soil degradation, Topsoil properties, Organic matter, Soil pH, Nitrogen levels.